Securitization and security of the Roma. Introduction to the special issue of Romano Džaniben - Ort, Jan (Romano džaniben, 2023)
The text defines the issue of the journal with the theme of securitization and security of the Roma. In doing so, it emphasizes the agency of the Roma themselves, i.e. their reactions to securitization discourses and practices, as well as their ways of understanding their own security. The author of the editorial presents the contributions contained in the thematic issue and selectively discusses the literature that has been published on related topics in the context of the Czech Republic and Slovakia.
Keywords: desecuritization; Roma; securitization; security